What Bertha Knows: Proprietary Narration in Katherine Mansfield's "Bliss" - Whiting, Kezia (Twentieth century literature, 2022)
How do we know what a character knows? What assumptions do we make about a character and their awareness when we read a text? How, in fact, does a text codify and construct knowledge, character, and thought? This essay addresses these questions in relation to Katherine Mansfield's short story, "Bliss." Most readers of "Bliss" assume that the protagonist, Bertha, knows nothing of her husband's apparent affair with a guest at their dinner party and even that she is unaware of her own burgeoning homosexual desire for this same guest. And yet the persistent ambiguity of Mansfield's free indirect style, at the least, allows Bertha to be read as knowing, deliberate, and complicit in her apparent ignorance. In conjunction with the text's critique of gender roles and expectations, Mansfield's free indirect style implicitly criticizes her reader's willingness to sideline Bertha's self-awareness. Mansfield's demonstration of the fungibility of the ownership of thoughts is underscored by her critique of Bertha's largely privileged lifestyle filled with possessions she is ultimately unable to fully possess.